PERANCANGAN KOTAK SAMPAH OTOMATIS LOGAM, ORGANIK DAN ANORGANIK BERBASIS IOT: PERANCANGAN KOTAK SAMPAH OTOMATIS LOGAM, ORGANIK DAN ANORGANIK BERBASIS IOT - Imro Mikel Selan; Arif Basuki; Mohammad Arsyad; Bagus Gilang Pratama; Karan Gunawan (Retii, 2022)
One of the environmental problems faced by people in Indonesia is environmental pollution as a result of public knowledge about waste management, as a result of public knowledge of types of waste and still mixing waste into one place. This research has designed a garbage bin system that is able to sort out the types of waste, namely metal, organic, and inorganic waste. It uses a capacitive proximity sensor, an inductive proximity sensor, and an esp 32 module. From the results of this study, it is proven that the automatic trash can that is designed can sort out metal, organic, and inorganic types of waste. Keywords: Design of metal, organic, and inorganic automatic garbage boxes.